2021
DOI: 10.1088/1361-6528/ac1752
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene oxide from agave fiber Tequilana Weber by hydrothermal method

Abstract: Lignocellulosic residues are an important biomass source in Mexico, which can be considered as starting materials for obtaining carbon materials. In this work, carbon materials were produced by pyrolysis of agave fiber (AF). The results obtained revealed that the hydrothermal process was successfully used for the synthesis of carbon fibers and subsequently potentiate the production of graphite sheets and graphene oxide (GO), after determining and optimizing the reaction conditions. The formation of graphite an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A recent study used lignocellulosic residue (gave fiber Tequilana Weber) as a substrate for the production of graphene oxide under hydrothermal process at higher temperature (800−1000 °C), and the thickness of the graphene oxide sheet was below 20 nm. 485 These authors have reported that the materials can be used for various purposes, including adsorption and catalysis without further purification. Zhang et al synthesized magnetic graphene from palm kernel shell (PKS) based on magnetization with the addition of two types of iron salts (FeSO 4 •7H 2 O and FeCl 3 •6H 2 O).…”
Section: Graphene and Other Carbonaceous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used lignocellulosic residue (gave fiber Tequilana Weber) as a substrate for the production of graphene oxide under hydrothermal process at higher temperature (800−1000 °C), and the thickness of the graphene oxide sheet was below 20 nm. 485 These authors have reported that the materials can be used for various purposes, including adsorption and catalysis without further purification. Zhang et al synthesized magnetic graphene from palm kernel shell (PKS) based on magnetization with the addition of two types of iron salts (FeSO 4 •7H 2 O and FeCl 3 •6H 2 O).…”
Section: Graphene and Other Carbonaceous Materialsmentioning
confidence: 99%
“…The synthesized graphene was used in lithium-ion batteries as an anode material, and it shows high reversible capacity, superior rate capability, and good cycling performance. A recent study used lignocellulosic residue (gave fiber Tequilana Weber ) as a substrate for the production of graphene oxide under hydrothermal process at higher temperature (800–1000 °C), and the thickness of the graphene oxide sheet was below 20 nm . These authors have reported that the materials can be used for various purposes, including adsorption and catalysis without further purification.…”
Section: Coupling Of Hydrothermal Treatment With Other Technologiesmentioning
confidence: 99%